Active myeloperoxidase: a promising biomarker to differentiate “acute” and “low-grade” peri-prosthetic joint infections from aseptic failures - Maritati, Martina; De Rito, Giuseppe; Rosta, Valentina; Cervellati, Carlo; Manfrinato, Maria Cristina; Zanoli, Gustavo Alberto; De Giorgio, Roberto; Guarino, Matteo; Costanzini, Anna; Contini, Carlo; Ning, Yu; Trampuz, Andrej; et al. (Frontiers in Microbiology, 2024)
The accurate distinction between periprosthetic joint infections (PJI) and aseptic failures (AF) is of paramount importance due to differences in treatment. However, this could be challenging by using the current criteria. Various synovial fluid biomarkers are being assessed to improve the diagnostic accuracy. Myeloperoxidase (MPO), an enzyme contained in the granules of neutrophils, may be a promising biomarker for PJI. Synovial fluids of 99 patients (n=65 PJI according to EBJIS criteria; n=34 AF) were collected in two specialized orthopedic centers. PJI were divided into acute (n=33) and low-grade (n=32) according to previously published classification. An activity assay specific for active MPO was performed in each sample. Ability of MPO to correctly discriminate patients with PJI from AF was determined by ROC analysis. The best discriminating cut-off value was determined by calculating the J Youden index. For all analyses, a P value<0.05 was considered statistically significant. Active MPO was higher in PJI than AF (P <0.0001). The ROC analysis revealed a significant area under the curve (AUC: 0.86; 95% CI: 0.78-0.93, P<0.0001). A cut-off value of 561.9 U/mL, with good sensitivity (0.69) and specificity (0.88), discriminated between AF and PJI (accuracy 75.76%, 95% CI: 66.11-83.81%, positive likelihood ratio 5.88, 95% CI: 2.31-14.98 and negative likelihood ratio 0.35, 95%CI: 0.24-0.51). No difference in MPO levels was found between acute and chronic low-grade PJI. The proposed assay appears to be a reliable and affordable tool for detecting the active MPO in synovial fluid, with promising characteristics of sensitivity and specificity in discriminating both acute and lowgrade PJI from AF. Further studies are needed to confirm MPO diagnostic cut-off values and validate their use in the routine clinical practice.